Arab Spring : Negotiating in the Shadow of the Intifadat - Zartman, I. William (Book collections on Project MUSE., 2015)
Ezzat (Cairo University), Amy Hamblin (SAIS), Abdullah Hamidaddin (King's College), Fen Hampson* (Carleton University), Roel Meijer (Clingendael), Karim Mezran (Atlantic Council), Bessma Momani (Waterloo University), Samiraital Pres (Cercle des Economistes Arabes), Aly el Raggal (Cairo University), Hugh Roberts (ICG/Tufts University), Johannes Theiss (College d'Europe), Siniša Vukovic (Leiden University), I. William Zartman* (SAIS-JHU). [* Indicates group members of the Processes of International, Negotiation (PIN) Program at Clingendael, Netherlands].